2010
DOI: 10.1194/jlr.m003665
|View full text |Cite
|
Sign up to set email alerts
|

A new HDL mimetic peptide that stimulates cellular cholesterol efflux with high efficiency greatly reduces atherosclerosis in mice

Abstract: Plasma HDLs are thought to protect against atherosclerosis via mechanisms related, in part, to reverse cholesterol transport (RCT) ( 1-3 ). This process involves removal of excess cholesterol from arterial foam-cells (i.e., cholesterol effl ux), followed by the transport of cholesterol to the liver for excretion in feces. Over-expression of apolipoprotein (apo) A-I, the major protein of HDL, in mice enhances RCT, inhibits atherosclerosis development, and stimulates regression of plaque lesions ( 4-8 ). Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(141 citation statements)
references
References 42 publications
(54 reference statements)
7
131
0
3
Order By: Relevance
“…Biophysical studies showed that the peptide possessed a high aqueous solubility that dissociated to trimers, dimers, and monomers upon dilution ( 127 ). The effi ciency of ATI-5261 in mediating macrophage cholesterol effl ux was similar to that of full-length apoA-I and apoE ( 65 ). Further, cholesterol effl ux was increased by treatment of cells with peptide in either a lipid-free form or as a phospholipid complex ( 65 ).…”
Section: Anti-atherogenic and Anti-inflammatory Effects Of Ac-he18a-nhmentioning
confidence: 78%
See 2 more Smart Citations
“…Biophysical studies showed that the peptide possessed a high aqueous solubility that dissociated to trimers, dimers, and monomers upon dilution ( 127 ). The effi ciency of ATI-5261 in mediating macrophage cholesterol effl ux was similar to that of full-length apoA-I and apoE ( 65 ). Further, cholesterol effl ux was increased by treatment of cells with peptide in either a lipid-free form or as a phospholipid complex ( 65 ).…”
Section: Anti-atherogenic and Anti-inflammatory Effects Of Ac-he18a-nhmentioning
confidence: 78%
“…A 10 amino acid peptide from the apoJ sequence was also shown to increase plasma cholesterol effl ux capacity in apoE Ϫ / Ϫ mice and improve HDL anti-infl ammatory properties ( 61 ). Other groups set out to improve the properties of existing peptide sequences ( 62,63 ) or to design entirely new sequences (64)(65)(66)(67).…”
Section: Demonstration Of Anti-atherogenic Effects Of Apoa-i Mimetic mentioning
confidence: 99%
See 1 more Smart Citation
“…4F can bind oxidized lipids with much higher affinity than apoAI (50), while its capacity to stimulate cholesterol efflux from macrophages is lower than apoAI on a per molar basis (80,81). Facts like these have led some to argue that the cholesterol efflux capacity of 4F is of secondary importance at best compared with its antioxidative capacity, as regards its effects on atherosclerosis (82). However, if 4F affects cholesterol efflux and macrophage RCT in vivo at the level of TICE rather than at the level of cholesterol efflux from macrophages themselves, as is suggested by results reported in Fig.…”
Section: F Increases Tice Through Duodenal Explants and Can Act As Amentioning
confidence: 99%
“…Future studies will be needed to determine if the fi ndings described here regarding the importance of dose independent of plasma peptide levels and the likely role of the intestine will also apply to other apoA-I mimetic peptides, particularly those which are thought to be more active on reverse cholesterol transport (19)(20)(21).…”
Section: If the Concentration Of Peptide In The Plasma Does Not Determentioning
confidence: 99%